Konsep Dasar, Faktor Pendukung dan Penghambat Strategi Pembelajaran Berbasis Masalah dan Implementasinya dalam Pendidikan - Ilat, Irene Preisilia; Gioh, Syalomitha; Moring, Eunike; Kosegeran, Leoni; Makananging, Marsyha (Institut Agama Kristen Negeri Manado, 2024)
Problem-based learning approaches are gaining interest in education due to their ability to develop critical thinking, problem-solving and collaboration skills. This article discusses the basic concept of problem-based learning (PBL) strategy, how it is implemented in various educational contexts, as well as the benefits gained by students and educators. In addition, the hindering and supporting factors that may be encountered in implementing PBL are also explored in this article, along with strategies to overcome these challenges.The literature study method was used to analyze this problem-based learning strategy. The research findings show that the implementation of problem-based learning strategy has a significant impact in the learning process. A thorough understanding of this strategy and its effective implementation, educators can shape a learning environment that motivates, puts students at the center of learning, and is in line with real-world demands.